Last Among Equals Hawaiian Statehood and American Politics - Bell, Roger (University of Hawai'i Press, 2018)
Last Among Equals is the first detailed account of Hawaii's quest for statehood. It is a story of struggle and accommodation, of how Hawaii was gradually absorbed into the politcal, economic, and ideological structures of American life. It also recounts the complex process that came into play when the states of the Union were confronted with the difficulty of granting admission to a non-contiguous territory with an overwhelmingly non-Caucasian population. More than any previous study of modern Hawaii, this book explains why Hawaii's legitimate claims to equality and autonomy as a state were frustrated for more than half a century.Last Among Equals is sure to remain a standard reference for modern Hawaiian and American political historians. As important, it will require a reevaluation of two commonly held myths: that of racial harmony in Hawaii and that of automatic equality under the Constitution of the United States.